Content Marketing Strategies in Sales Management: A Case Study in a Botica de Trujillo – Peru (LACCEI, 2024)
The present research applied with a quantitative approach, with a pre-experimental design, had the purpose of determining the influence of the implementation of content marketing strategies in the sales management of the Botica Salud Farma of Trujillo in 2022, for which it was used an observation sheet, which went through a reliability process through the sofware SPSS ver. 25. To measure the level of productivity, sales growth and sales effectiveness, values before and after the implementation of content marketing strategies, for which the methodology proposed by Monacchi was used as a basis: research, plan, design, disseminate and evaluate the same one that was executed during the months of October and November, 2022 making a comparison with previous months that were May and June the main results of the sales management indicators, an increase in the level of productivity was detected by 5 %, sales growth of 213% and sales effectiveness of 7%. It is concluded that the influence of the implementation of content marketing strategies was reflected in only one indicator of the sales management of Botica Salud Farma.